The development of an evidenced-based submaximal cycle test designed to monitor and predict cycling performance : the Lamberts and Lambert submaximal cycle test (LSCT) - Lamberts, Robert Patrick (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Includes abstract.